Antiretroviral drug adherence among patients with HIV/AIDS based on socio-demographic characteristics - Mela Liberti Octoriani Simaremare; Suharmanto Suharmanto; Bayu Anggileo Pramesona; Susianti Susianti; Betta Kurniawan (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background : The government has set a target for accelerating the prevention of HIV/AIDS in Indonesia, namely zero new infections, zero people dying from HIV/AIDS, and zero stigma and discrimination. Stigma against people living with HIV has a major impact on HIV/AIDS prevention and control programs, including the quality of life for people living with HIV. Good knowledge will reduce the stigma that appears. Adherence to the use of ARV (antiretroviral) is one of the factors that can significantly extend the life expectancy of people living with HIV (people living with HIV AIDS). ARVs work against infection by slowing the reproduction of HIV in the bodyPurpose: To identify the factors that influence the adherence of people living with HIV to taking ARVs. Method: This is an observational, descriptive, and quantitative research project with a cross-sectional approach. The research will be conducted at the Sukabumi Health Center in Bandar Lampung in 2021. The population in this project is 103 HIV patients. The sampling technique used is total sampling.Results: Meanwhile, there are more PLHIV patients from urban areas than from rural areas. People living with HIV usually need ARV if the CD4 level is 350 mm3.Conclusion: The univariate variables of age group, occupation, education, gender, and origin of residence did not affect whether people living with HIV were non-adherent to treatment.